A Regional Analysis of the Relationship Between Housing Affordability and Business Growth. Issue 4 (November 2021) - Oluku, Uche; Cheng, Shaoming
Using U.S. Census data for the period 2010 to 2016, for 383 metropolitan statistical areas (MSAs) and 3, 137 counties nationwide, the authors examine the relationship between housing affordability and business growth in three industrial sectors: Retail, Information, and Professional Services. Housing affordability is measured by the percentage of cost-burdened homeowners and renters, defined as the proportion of households paying 30% or more of gross income toward owners' costs or rents. The results of a generalized method of moments dynamic panel regression analysis are mixed using MSA-level data. However, using county-level data, the authors find compelling evidence that an increase in homeowner and renter cost burden has a statistically significant adverse effect on business growth in all three business sectors. For instance, over a 7-year period, if housing unaffordability increases by 1 percentage point annually, the number of Professional Services establishments is expected to shrink by 90, 248 across 3, 137 counties nationwide.